Toxicological evaluation of a novel umami flavour compound: 2-(((3-(2, 3-Dimethoxyphenyl)-1H-1, 2, 4-triazol-5-yl)thio)methyl)pyridine. (2016) - Karanewsky, Donald S.; Arthur, Amy J.; Liu, Hanghui; Chi, Bert; Ida, Lily; Markison, Stacy
Abstract: A toxicological evaluation of a umami flavour compound, 2-(((3-(2, 3-dimethoxyphenyl)-1 H -1, 2, 4-triazol-5-yl)thio)methyl)pyridine (S3643; CAS 902136-79-2), was completed for the purpose of assessing its safety for use in food and beverage applications. S3643 undergoes extensive oxidative metabolism in vitro with rat microsomes producing the S3643-sulfoxide and 4′-hydroxy-S3643 as the major metabolites. In incubations with human microsomes, the O -demethyl-S3643 and S3643-sulfoxide were produced as the major metabolites. In pharmacokinetic studies in rats, the S3643-sulfoxide represents the dominant biotransformation product. S3643 was not found to be mutagenic or clastogenic in vitro, and did not induce micronuclei in CHO-WBL cells. In subchronic oral toxicity studies in rats, the no-observed-adverse-effect-level (NOAEL) for S3643 was 100 mg/kg bw/day (highest dose tested) when administered in the diet for 90 consecutive days.